Acute whole body vibration training increases vertical jump and flexibility performance in elite female field hockey players - Cochrane, D. J.; Stannard, S. R. (British Journal of Sports Medicine, 2005)
Objective: To quantify the acute effect of whole body vibration (WBV) training on arm countermovement vertical jump (ACMVJ), grip strength, and flexibility performance.